Governance Quality, Intrinsic and Extrinsic Factors on Tax Compliance: Evidence from Expert Individual Taxpayers - Indah Masri; Tryas Chasbiandani; Diandra Kamila Rasyid; Nur’Aini (Jurnal Reviu Akuntansi dan Keuangan, 2025)
Purpose: This research aims to examine factors that can increase the level of taxpayer compliance both from an intrinsic and extrinsic perspective and the role of governance quality in this relationship. The intrinsic factor is tax morale and the extrinsic factor is tax knowledge. Methodology/approach: This research using existing data in the field in the form of surveys allows a broader exploration of the effects of social norms on tax compliance behavior, especially for expert individual taxpayers, who are professionals who have a high level of education on the motivation of reasonable levels of taxpayer compliance, which are intrinsic (tax morals) and extrinsic (tax knowledge). Data processing uses smart PLS 4.0 with Structural Equation Modeling (SEM) equations. Findings: The research results in the first model, namely without moderation, show that tax morale, tax knowledge, and governance quality significantly positively affect increasing tax compliance. However, the second model, namely moderating governance quality with tax morale and tax knowledge, shows that the results have a significant negative effect on tax compliance, which means that the role of governance quality can weaken the influence of tax morale and tax knowledge on the level of taxpayer compliance. Practical implications: This research can analyze various factors of taxpayer behavior, incredibly expert individual taxpayers, regarding taxpayer compliance. Originality/value: Novelty from this research shows that the behavior of individual taxpayers, especially experts who are professionals with a high level of education, shows that various factors of taxpayer behavior can influence the level of taxpayer compliance, especially in the condition of governance quality.